Kolaborasi Guru dan Orang Tua dalam Mengembangkan Literasi Bahasa Ramah Anak pada Anak Usia Dini - Liana Rochmatul Wachidah; Purnomo Ahmad Putikadyanto, Agus (Institut Agama Islam Negeri Madura, 2024)
Literacy in the early stages of life is very important for children. Language literacy in early childhood is not just about reading and writing, but also involves understanding, speaking and listening skills. Differences in literacy development patterns in children are adjusted to the language abilities they have. The aim of this research is to describe the results of collaboration between the roles of teachers and parents in developing child-friendly language literacy in early childhood. The method used in this research is qualitative with a descriptive approach. Data sources were obtained from teachers and guardians of Al Hidayah Kindergarten Wonorejo students. Data in the form of interview transcripts and questionnaire results. Data collection techniques used interviews and questionnaires. The data analysis techniques in this research are data reduction, verification and conclusions. The results of this research are about close collaboration between parents and teachers creating a holistic learning environment for children through the application of the Read It Again-Prek! (RIA) which aims to facilitate the development of early childhood language and literacy skills in 4 main areas, namely: vocabulary, stories, phonological awareness, and written knowledge. Therefore, open communication is needed to share information, support and respect each other's roles (teachers and parents), and create a conducive child-friendly literacy environment.